The Axiological Aspects of Neoliberalism and Education - Potulicka, Eugenia (Paedagogia Christiana, 2026)
The article deals with problems connected with neoliberalism, including the meanings of the term, its perceived virtues, its vision of humankind, homo economicus and the influence of global corporations’ on education. The author concludes that neoliberalism degrades all groups of people and educational systems worldwide.